Copy Number Variations of CEP63, FOSL2 and PAQR6 Serve as Novel Signatures for the Prognosis of Bladder Cancer - Cai, Zhao; Chen, Huang; Bai, Jingqiao; Zheng, Yang; Ma, Jianhui; Cai, Xiongwei; Liu, Yu; Zhang, Kaitai; Shou, Jianzhong; Gao, Yanning (Frontiers in Oncology, 2021)
Background: Finding effective prognostic signatures is of great urgency due to the high recurrence rate of bladder cancer (BC). Although a lot of genetic alterations are involved in the carcinogenesis, none of them were referred in the current risk group stratifications. In this study, we aimed to find significant copy number variations (CNVs) to predict recurrence risk for BC patients. Methods: 65 tumor samples were used to find CNVs with high aberration frequencies by array-based comparative genomic hybridization. Candidates were validated in independent groups of BC tumor samples (n=219) and urine samples (n=123). 3D digital PCR was applied for detecting accurate gene copy numbers in BC urine. Results: CNVs of CEP63, FOSL2 and PAQR6 with high aberration frequencies (67.7%, 56.9% and 60.0%, respectively) were found in BC tumors. Copy numbers of CEP63, FOSL2 and PAQR6 were gained in 219 tumor samples. CNVs of CEP63 and FOSL2 were correlated with advanced tumor stage and high grade. Retrospective analysis (median follow-up time: 69 months) revealed that CNVs of CEP63, FOSL2 or PAQR6 were independent prognostic factors for disease-free survival (DFS). Models for predicting recurrence risk were constructed based on CNVs of three genes. Patients with high prognostic indexes tended to have poor DFS. Copy number gains of CEP63 and FOSL2 in urine were found to be significantly correlated with poor DFS of NMIBC patients. Conclusions: CNVs of CEP63, FOSL2 and PAQR6 were capable of predicting recurrence and may serve as promising signatures for prognosis of BC.